THE INFLUENCE OF WORK DISCIPLINE AND COMPETENCE ON EMPLOYEE PERFORMANCE AT THE INDONESIAN NATIONAL POLICE MEDICAL AND HEALTH CENTER (PUSDOKKES POLRI) - Rahayu, Niniek (BAIK Publishers, 2025)
This study aims to analyze the influence of work discipline and competence on employee performance, both partially and simultaneously. This study was conducted on 100 employees selected through a purposive sampling method. Data analysis techniques used included validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results showed that partially, work discipline had a positive and significant effect on performance with a calculated t-value of 9.987, while competence also had a positive and significant effect on performance with a calculated t-value of 10.708. This value is greater than the t-table (1.985) with a significance level of 0.000. Simultaneously, work discipline and competence significantly influenced employee performance with a calculated F-value of 78.435, greater than the F-table (3.09) with a significance level of 0.000. The coefficient of determination indicates that work discipline and competence together explain 67.5% of the performance variable, while the remaining 32.5% is influenced by factors outside this study. These research findings emphasize the importance of managing work discipline and developing employee competencies to optimally improve performance. Therefore, companies are expected to improve training, discipline supervision, and create a supportive work environment so that employees can work professionally, productively, and in accordance with organizational goals